Pengaruh Intensitas Modal, Intensitas Aset Tetap, dan Tingkat Utang terhadap Manajemen Pajak (Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek IndonesiaTahun 2019-2022) - Anggi Kirana Septiani; Aloysius Harry Mukti; Triana Yuniati (Draf Solusi Indonesia, 2024)
The purpose of this study was to test and analyze the influence of capital intensity, fixed asset intensity, and leverage on tax management. This research method uses quantitative research methods, with secondary data sources using financial data and the company's annual reports. The population in this study is all companies listed on the Indonesia Stock Exchange in the consumer non-cyclicals sub-sector in 2019-2022 period that produced 195 samples of corporate financial statements using purposive sampling techniques. The analysis methods applied in this study are descriptive statistical tests, classical assumption tests, correlation test, multiple linear regression tests, and hypothesis tests. The results of this study indicate that capital intensity has a positive effect on tax management, fixed asset intensity has a positive effect on tax management, and leverage has a negative effect on tax management.